Validation of the Behavioral Regulation Sport Questionnaire in portuguese athletes - Monteiro, Diogo (2018)
The purpose of this study was to translate and validate the Behavioural Regulation in Sport Questionnaire (BRSQ), using confirmatory factor analysis, with a total sample formed of 940 athletes (n = 232 female and n = 708 male), from different sports: football (n = 623), basketball (n = 202), athletics (n = 43) and swimming (n = 72), participating in the categories of iniciated, juvenile, junior and senior, with an average of (M = 17.63; SD = 4.32) years. The results support the suitability of the model (6 factors/24 items), showing an adjustment fit to the data for this sample (S-B χ² = 1308; df = 237; p = .001; SRMR = .059; NNFI = .895; CFI = .901; RMSEA = .066; 90%IC RMSEA = .066-.070). As for the individual parameters, the items factorial weights present acceptable values, factor loadings varied (between .49 to .84), and acceptable values of internal reliability, convergent and discriminant validity’s. Those findings allow us to conclude that the Portuguese version of the BRSQ can be used with high confidence to evaluate de motivation regulation in the sport context.